Influência da dosagem racional do concreto seco na produção de peças de concreto para pavimentação intertravada - Pinheiro, Rafael Severo (2015)
The concrete blocks for interlocking paving, also known as pavers, have been used for decades in some countries, but in Brazil its use only gained popularity in recent years. Still, the lack of quality control and the failure to meet the requirements of existing rules not only bring considerable financial losses to cement artifacts industries, but also reduce costumer confidence in the product. Besides, with the expansion of brazilian construtction ocurred in the last years, the market became more competitive, requiring more quality of products and reduction of waste. The problem of lack a proper mix design and quality control is normally attributed to the erraneous idea that this process is lengthly and expensive. This paper presentes technical and financial comparisions between pavers produced using and empirical dosage method, and a rational one. It also demonstrates the influence of the aplication of this rational dosage method in the production of concrete blocks, and the financial gains of its application in the cement artifacts industry.